Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1371/journal.pone.0037778
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis Incidence and Re-Infection among Young Women – Behavioural and Microbiological Characteristics

Abstract: BackgroundThis study aimed to estimate rates of chlamydia incidence and re-infection and to investigate the dynamics of chlamydia organism load in prevalent, incident and re-infections among young Australian women.Methods1,116 women aged 16 to 25 years were recruited from primary care clinics in Australia. Vaginal swabs were collected at 3 to 6 month intervals for chlamydia testing. Chlamydia organism load was measured by quantitative PCR.ResultsThere were 47 incident cases of chlamydia diagnosed and 1,056.34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
105
3
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 43 publications
(59 reference statements)
8
105
3
1
Order By: Relevance
“…Serovars E and F are generally found to be predominant in most countries, including Australia, Netherlands, and Sweden (28)(29)(30)(31)(32). Using omp1 PCR-based restriction fragment length polymorphism genotyping, Lan et al (33) reported that in women Ͻ30 years old, serovars D (4/21 asymptomatic women) and I (4/21 asymptomatic women) were associated with asymptomatic infection, while serovar G was associated with symptomatic infection (4/30 symptomatic cases).…”
Section: Chlamydial Serovars Can Associate With Repeat Infection and mentioning
confidence: 99%
See 1 more Smart Citation
“…Serovars E and F are generally found to be predominant in most countries, including Australia, Netherlands, and Sweden (28)(29)(30)(31)(32). Using omp1 PCR-based restriction fragment length polymorphism genotyping, Lan et al (33) reported that in women Ͻ30 years old, serovars D (4/21 asymptomatic women) and I (4/21 asymptomatic women) were associated with asymptomatic infection, while serovar G was associated with symptomatic infection (4/30 symptomatic cases).…”
Section: Chlamydial Serovars Can Associate With Repeat Infection and mentioning
confidence: 99%
“…Batteiger et al studied a longitudinal cohort of 210 adolescent women (14 to 17 years old) in the United States and found that 121 experienced repeat infections (79). In a longitudinal cohort in Australia, 1,116 women (16 to 25 year old) were followed up and 14 reinfections were observed in a total of 81 women who were at risk of repeat infection (3 of these had two episodes of reinfection) (cumulative risk over 12 months of 20.3%; 95% confidence interval [CI], 13.2 to 37.6%) (32). Interestingly, in this study in Australia, the organism load was lower in reinfections than in prevalent infections detected at the study baseline (32) but there were no associations between patient characteristics and reinfection (32) (possibly because the study was underpowered to detect an effect).…”
Section: Repeat Infection and Infertilitymentioning
confidence: 99%
“…While background antibiotic use may impact the transmission of STIs on a population level, it may also impact clinical practices since it affects the outcome of an STI diagnostic test and may interact with subsequent treatment. Studies among men and young women receiving antenatal, general practitioner, or sexual health care in Australia demonstrated that recent antibiotic use was associated with a lower prevalence and incidence of genital C. trachomatis (1,15,16,17). However, the specific antibiotic agents were not studied.…”
mentioning
confidence: 99%
“…Repeated detection of chlamydia after screening and treatment is common. About 20-30% of treated women followed prospectively have a repeat positive chlamydia test by 12 months [198,199], despite routine partner notification efforts. In a prospective cohort study of young women who were screened for chlamydia every three months, the point prevalence of chlamydia remained at around 10% throughout follow up [200].…”
Section: Impact Of Chlamydia Screening On Transmission Of Chlamydiamentioning
confidence: 99%